Modeling of laminar-turbulent transition in a turbine rear structure - Augusto Arias, Diego; Dev Roy, Shameek (My University, 2021)
The turbine rear structure (TRS) of modern aircraft gas turbine engines have several significant role, one of which is de-swirling the outlet flow coming from the Low Pressure Turbine (LPT) located upstream. Furthermore, the Outlet Guide Vane (OGV) in the TRS provides a structural support between the aft bearing support and main engine case. Other than de-swirling the flow, the TRS-OGV is mechanically and thermally loaded due to the hot outlet gases coming from LPT, which requires the OGV to be designed robustly. The TRS facility in Chalmers University, has a capability of operating over a wide range of Reynolds number, which allows several modes of transition, which in turn affects the aerodynamic and aerothermal performance. This thesis presents a tuned case-specific numerical investigation on the laminar-turbulent transition flow structures in the Turbine Rear Structure- Outlet Guide Vane (TRS OGV). The work includes the processes and results of matching the laminar turbulent transition in the TRS OGV using RANS-CFD with SST k-ω turbulence model and the Langtry-Menter γ-θ transition model. Experimental data for a certain case was used for ambient and boundary conditions for the inlet, outlet, turbulence decay and surface heat transfer. The numerical results obtained, match the experimental verification data considerably well.
Keywords: Blade Loading, Boundary Layer, Heat Transfer Coefficient, Momentum Thickness Reynolds Number, Outlet Guide Vane, Swirl Angle, Transition Onset, Turbulent Decay, Turbulent Intensity, y+